PENGARUH CAR, BOPO, NPF, DAN CSR DISCLOSURE TERHADAP PROFITABILITAS PERBANKAN SYARIAH - Nurul Rahmi; Ratna Anggraini (Jurnal Ilmiah Wahana Akuntansi, 2013)
This study aims to determine the influence of CAR, BOPO, NPF, and CSR Disclosure on Profitability Sharia Banks. Factors tested in this study are CAR, BOPO, NPF, and CSR Disclosure as independent variables while ROA as dependent variables. This study sample consist of three Sharia Banks which listed in Bank of Indosesia year 2009-2011. The data used in this study is secondary data and sample selection by using purposive sampling method. Analysis tool used is multiple linear regression analysis at a significance level 5%. The results of stimulnaoys and partial hypothesis testing used showed that the four independent variables which are independent CAR, BOPO, NPF, and CSR Disclosure affect on ROA. Keywords: CAR, BOPO, NPF, CSR Disclosure,ROA